APP intracellular domain derived from amyloidogenic β- and γ-secretase cleavage regulates neprilysin expression - Grimm, Marcus O.; Mett, Janine; Stahlmann, Christoph P.; Grösgen, Sven; Haupenthal, Viola J.; Blümel, Tamara; Hundsdörfer, Benjamin; Zimmer, Valerie C.; Mylonas, Nadine T.; Tanila, Heikki; Müller, Ulrike; Grimm, Heike S.; et al. (Frontiers in Aging Neuroscience, 2015)
Alzheimer´s disease (AD) is characterized by an accumulation of Amyloid-β (Aβ), released by sequential proteolytic processing of the amyloid precursor protein (APP) by β- and γ-secretase. Aβ peptides can aggregate, leading to toxic Aβ oligomers and amyloid plaque formation. Aβ accumulation is not only dependent on de novo synthesis but also on Aβ degradation. Neprilysin (NEP) is one of the major enzymes involved in Aβ degradation. Here we investigate the molecular mechanism of NEP regulation, which is up to now controversially discussed to be affected by APP processing itself. We found that NEP expression is highly dependent on the APP intracellular domain (AICD), released by APP processing. Mouse embryonic fibroblasts devoid of APP processing, either by the lack of the catalytically active subunit of the γ-secretase complex (presenilin (PS) 1/2) or by the lack of APP and the APP-like protein 2 (APLP2), showed a decreased NEP expression, activity or protein level. Similar results were obtained by utilizing cells lacking a functional AICD domain (APPΔCT15) or expressing mutations in the genes encoding for PS1. AICD supplementation or retransfection with an AICD encoding plasmid could rescue the down-regulation of NEP further strengthening the link between AICD and transcriptional NEP regulation, in which Fe65 acts as an important adaptor protein. Especially AICD generated by the amyloidogenic pathway seems to be more involved in the regulation of NEP expression. In line, analysis of NEP gene expression in vivo in six transgenic AD mouse models (APP and APLP2 single knock-outs, APP/APLP2 double knock-out, APP-swedish, APP-swedish/PS1Δexon9 and APPΔCT15) confirmed the results obtained in cell culture. In summary, in the present study we clearly demonstrate an AICD-dependent regulation of the Aβ-degrading enzyme NEP in vitro and in vivo and elucidate the underlying mechanisms that might be beneficial to develop new therapeutic strategies for the treatment of AD.